“Land Tenure Problems and the Rural Youth of Rwanda” The Case of the District of Kamonyi - Dushimimana, Jean de Dieu (My University, 2007)
This study aimed to investigate land tenure problems experienced by the youth of the rural areas of Rwanda. The study targeted the young men and women who have experienced several land problems in terms of land access and ownership, in the district of Kamonyi. The youth’s land tenure problems, their nature, their causes and their effects on youth’s lives were collected and analysed. The study also aimed to analyse the National Land Policy document of 2004 by looking at three aspects namely the land redistribution, group settlement, and the participation of other different government departments, civil society and youth in particular in the policy process in order to see how it deals with land tenure problems facing the rural youth. In order to collect and analyse data, this study used a qualitative method. The use of this method was motivated by its quality of providing information that one can not get with a questionnaire. Moreover, the qualitative method enables to collect and analyse in-depth information on a smaller group of respondents and enables the researcher to participate in data collection. Documentary analysis, observation, in-depth interviews and the focus group discussion were the techniques used to gather data. The study population was made of 20 young people who have experienced the land problems and 10 key informants. The concept of participation, the human needs, and the resource scarcity and conflict theories framed this work. Participation means that all the beneficiaries of a project must be involved in the decision-making, implementation and control process of the programme. As the concept of participation highlights that, problems of poverty among people, specifically young people, are solved when they are involved in planning and implementation of projects that affect their lives, the same concept was used in the current study to investigate whether rural young people have been involved in the land reform process. Youth participation should be taken into account for achieving positive development. When youth are involved in decision-making, they experience social justice as full citizens and their problems are quickly solved. Participation should be achieved from below whereby all members of the community participate in the decision-making on the projects that affect their lives. In other words, developmental projects must take into account the needs and views of beneficiaries and the latter must be empowered in order to achieve effective results. Many development policies fail in Africa and in Rwanda due to the lack of involving beneficiaries or taking into account their views. In addition, the natural resources must be equally shared by all the citizens without any social inequality, in order to avoid intractable-conflicts. People’s basic needs should be met because where some basic needs such as water, land, education, healthcare, shelter are not given, conflicts arise. Where resources are not sufficient to fit with all people in need, the properties’ ownership should be collective rather than individual. The key findings of the study show that the ways of land access and ownership in Kamonyi are mainly, land acquisition through inheritance, through land purchase through land gifted, and through land allocation by the government. Youth experience mainly the problem of landlessness due to the family land scarcity, inequalities between the elites and the poor in terms of land ownership, the increasing number of heirs since women have been included among heirs, the problem of polygamy and the lack of a known father. Many households have no title-deeds, some male children and their fathers become reluctant to recognise women’s inheritance rights, conflicts around land boundaries between neighbours and conflicts between children and their parents due to the lack of inheritance become endless. The national Land Policy of 2004 that intends to solve all the above land tenure problems bears contradictions related to its aim of achieving equity and equality and productivity at the same time. While the policy intends to establish a land tenure system that guarantees tenure security for all Rwandans, it also states that not every Rwandan will possess a plot of land of his own. In addition, it states that former refugees, professionals pastoralists and farmers, and those who will be able to apply for land showing interest in land development will be given land through the redistribution programme, which means that those who are not able to make a consistent application for land or do not belong to former refugees families will not acquire land. In addition the policy process has not been participative at large; rather it has been limited in the hands of elites, rural dwellers especially youth have not been consulted while they are familiar with land related problems. The group settlement is a good alternative but it bears ambiguity because it is silent on the youth’s lives and on who is accountable to build houses in villages.
Student Number: 0514015W - MA research report - School of Social Sciences - Faculty of Humanities
Keywords: Land Tenure Problems; Rural Youth; Rwanda; Kamonyi; causes; effects; National Land Policy document of 2004; land redistribution; group settlement; land reform process